Weed germinable seedbanks of rice-wheat systems in the Eastern Indo-Gangetic Plains: Do tillage and edaphic factors explain community variation? - Lowry, Carolyn J.; Brainard, Daniel C.; Kumar, Virender; Smith, Richard G.; Singh, Madhulika; Kumar, Pankaj; Kumar, Ajay; Kumar, Vipin; Joon, Rajiv K.; Jat, Raj K.; Poonia, Shishpal; Malik, Ram K.; et al. (Wiley, 2021)
Zero tillage (ZT) is widely promoted throughout India's Eastern Indo‐Gangetic Plains (IGP) because of its potential to increase wheat productivity and resilience to abiotic stresses. Weeds remain a major barrier to ZT adoption, yet it remains unclear how ZT will influence weed communities in the Eastern‐IGP. The primary objective of this study was to characterise the composition of the germinable weed seedbank sampled just prior to the wheat phase of rice–wheat farms in Bihar and Eastern Uttar Pradesh, and examine whether adoption of ZT wheat has shifted weed community composition compared to conventional tillage (CT). Additionally, we examined whether edaphic properties and topography (upland vs. lowland) explain variation in germinable weed seedbank communities. In December 2014, we evaluated the germinable seedbank from 72 fields differing in their historic (>=3 year) tillage practices (ZT vs. CT) in three regions: Samastipur–Vaishali–Muzaffarpur (SVM), Ara–Buxar and Maharajgunj–Kushinagar. Weed community composition and species richness varied by region and topography. ZT adoption was associated with lower relative density of Chenopodium album in the germinable seedbank and lower emergence of Phalaris minor seedlings within farmers’ fields. In upland topographies of the SVM region, ZT adoption was also associated with greater relative abundance of Solanum nigrum in the weed seedbank. However, differences between tillage systems in individual species were not large enough to result in detection of differences at the whole‐community level. Variation in edaphic properties, most notably soil texture and pH, explained 51% of the variation in the weed seedbank community. Our work suggests several frequent but poorly understood species (e.g. Mazus pumilus and Grangea maderaspatana) in Eastern IGP for which future research should quantify their effects on crop yields. Finally, future work surveying weed species abundance at harvest could further determine the dominant problematic species in these regions.